3D Printing Errors Detection During the Process - Florin-Bogdan MARIN; Mihaela MARIN (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
Automated error detection in 3D printing is an important challenge that impacts not only the quality of the final parts but also operational efficiency, helping to minimize wasted time and material. Certain types of errors can even result in printer malfunctions. A widely used solution for monitoring the printing process involves employing a webcam to observe the process in real time, either alerting the operator or halting the print if an issue is detected. In this paper, a computer vision algorithm able to detect specific errors is proposed.